Neurological diseases caused by coronavirus infection of the respiratory airways. Issue 4 (December 2020) - Ahmed, Waqas; Khan, Adeel; Sundar, Wish Hal; Naseem, Humaira; Chen, Wanghao; Feng, Jia; Durrani, Samran; Chen, Lukui
Infections of the central nervous system (CNS) infections are critical problems for public health. They are caused by several different organisms, including the respiratory coronaviruses (CoVs). CoVs usually infect the upper respiratory tract causing the common cold. However, in infants, and in elderly and immunocompromised persons, they can also affect the lower respiratory tract causing pneumonia and various syndromes of respiratory distress. CoVs also have neuroinvasive capabilities because they can spread from the respiratory tract to the CNS. Once infection begins in the CNS cells, it can cause various CNS problems such as status epilepticus, encephalitis, and long‐term neurological disease. This neuroinvasive properties of CoVs may damage the CNS as a result of misdirected host immune response, which could be associated with autoimmunity in susceptible individuals (virus‐induced neuro‐immunopathology) or associated with viral replication directly causing damage to the CNS cells (virus‐induced neuropathology). In December 2019, a new disease named COVID‐19 emerged which is caused by CoVs. The significant clinical symptoms of COVID‐19 are related to the respiratory system, but they can also affect the CNS, causing acute cerebrovascular and intracranial infections. We describe the possible invasion routes of coronavirus in this review article, and look for the most recent findings associated with the neurological complications in the recently published literature.